2015
DOI: 10.1093/mnras/stu2673
|View full text |Cite
|
Sign up to set email alerts
|

How well can cold dark matter substructures account for the observed radio flux-ratio anomalies

Abstract: Discrepancies between the observed and model-predicted radio flux ratios are seen in a number of quadruply-lensed quasars. The most favoured interpretation of these anomalies is that CDM substructures present in lensing galaxies perturb the lens potentials and alter image magnifications and thus flux ratios. So far no consensus has emerged regarding whether or not the predicted CDM substructure abundance fully accounts for the lensing flux anomaly observations. Accurate modelling relies on a realistic lens sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
150
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(166 citation statements)
references
References 117 publications
(225 reference statements)
13
150
3
Order By: Relevance
“…These smooth-lens relations are violated if there are intervening structures or substructures in the lens giving rise to flux-ratio anomalies, which probe the total amount of mass in structures along the line of sight to the lens [341,343,344]. Flux-ratio anomalies have been observed in several quadruply-lensed quasars but dark substructures alone are insufficient to explain the observed anomalies [345], implying that other effects such as inadequate lens modelling may be at work. With better modelling of the lens (including stellar discs and luminous satellites), it has been possible to set a lower limit to the mass of a thermal WDM particle (see [346] and Harvey et al, in preparation), similar to the limits from satellite counts discussed above and also to those derived from the observed inhomogeneity of the gas distribution at high redshift probed by the Lyman-α forest [347].…”
Section: Astrophysical Tests Of the Nature Of The Dark Mattermentioning
confidence: 99%
“…These smooth-lens relations are violated if there are intervening structures or substructures in the lens giving rise to flux-ratio anomalies, which probe the total amount of mass in structures along the line of sight to the lens [341,343,344]. Flux-ratio anomalies have been observed in several quadruply-lensed quasars but dark substructures alone are insufficient to explain the observed anomalies [345], implying that other effects such as inadequate lens modelling may be at work. With better modelling of the lens (including stellar discs and luminous satellites), it has been possible to set a lower limit to the mass of a thermal WDM particle (see [346] and Harvey et al, in preparation), similar to the limits from satellite counts discussed above and also to those derived from the observed inhomogeneity of the gas distribution at high redshift probed by the Lyman-α forest [347].…”
Section: Astrophysical Tests Of the Nature Of The Dark Mattermentioning
confidence: 99%
“…However, much lower masses, down to ∼10 6 M , may be probed through strong gravitational lensing, either via flux-ratio anomalies (e.g. Mao & Schneider 1998;Xu et al 2009Xu et al , 2015, or detectable perturbations of observed Einstein rings by substructures in the lens itself or along the line of sight (Mao & Schneider 1998;Metcalf & Madau 2001;Dalal & Kochanek 2002;Vegetti et al 2012Vegetti et al , 2014). On these scales, different dark matter models may be clearly distinguished, provided that the expected abundances and distributions of substructures for different models can be reliably predicted.…”
Section: Introductionmentioning
confidence: 99%
“…The same problem was also considered in Metcalf, Zhao (2002). At the same time another analysis by Xu et al (2009Xu et al ( , 2015 showed that the population of substructures predicted by numerical methods is insufficient to explain the observed anomalies in the ratio of fluxes of lensed images. These anomalies can be probably explained by the presence of complex baryonic structures in lensing galaxies and also by a presence of dark subhaloes on the line of sight.…”
Section: Another Scientific Tasksmentioning
confidence: 99%